Reactualization of National Resilience: A Historical and Conceptual Study (Jurnal Lemhannas RI, 2024)
Purpose: This study aims to explore the evolution and strategic importance of the concept of national resilience in Indonesia, highlighting its holistic nature and relevance to the National Lemhannas RI and the 2025-2045 RPJPN (National Long-Term Development Plan).Study Design/Methodology/Approach: The research adopts a qualitative approach, utilizing semi-structured interviews to accurately assess changes in the national resilience concept since 1964. This method provides an in-depth understanding of how the concept has adapted over time.Findings: The study reveals that the concept of national resilience has evolved in response to the increasing complexity and scope of strategic threats. These developments underscore the importance of continually adapting national resilience to meet current and future challenges.Originality/Value:This study offers valuable insights into the historical and contextual factors shaping Indonesia’s national resilience. It emphasizes the crucial role of the National Lemhannas RI as a center of excellence, contributing to the realization of a sovereign, independent, and resilient Indonesia
Keywords: National Resilience Concept; Sustainability of National Resilience; Historical and Contextual Factors; Conceptual Research; Application of the National Resilience Concept